The Role of Text To Speech Assistive Technology to Improve Reading Ability in E-Learning for ADHD Students - Dessy Rizky Nuraini Herawati; Wiwik Widajati; Endang Pudjiastuti Sartinah (Department of Special Education, 2022)
This study aims to determine the role of text to speech assistive technology on the reading ability of ADHD students in learning using e-learning. The ability of ADHD students who have impulsive and hyperactive behavior shows that students who are diagnosed will have difficulty focusing on one thing as a result of coordination functions and emotional responses that affect learning abilities, especially in reading. To improve reading skills, the use of assistive text to speech technology is needed by students during e-learning. The purpose of this study was to determine the role of text to speech assistive technology to improve the reading ability of ADHD students in reading spelling of words, with a clear voice and straightforward word emphasis. The method used in this study is Single Subject Research (SSR) using the ABA technique. Instruments to determine the level of reading ability of ADHD students are observation and documentation. The results showed that the role of text to speech assistive technology to improve reading skills in e-learning for ADHD students made progress in spelling words and with clear vowels and straightforward word emphasis. It can be concluded that the role of text to speech assistive technology to improve reading skills in e-learning for ADHD students is highly recommended to be applied in every e-learning lesson. It can be concluded that the role of text to speech assistive technology to improve reading skills in e-learning for ADHD students is highly recommended to be applied in every e-learning lesson.